Accurate Perception of Rock Strata Movement for Environmental Protection in Coal Mining: Taking Thick and Hard Roof Cooperative Control as an Example - Tong Zhao; Changyou Liu; Kaan Yetilmezsoy; Majid Bahramian; Peilin Gong (Advances in Civil Engineering)
Accurate perception of the key stratum instability can improve the safety of coal mining and also provide a basis for alleviating overlying rock strata destruction and environmental disturbance. To efficiently evaluate the instability of the key stratum and its threat to safe mining and environmental protection, the fracture characteristics and weakening mechanisms were studied through physical simulation, theoretical analysis, and field measurement. A scheme and the parameters of confined blasting in water-filled deep hole presplit technology (CBWDHPT) for thick and hard roof (THR) weakening were proposed. Research studies showed that, after the THR fractured into large blocks, the subsequent sliding instability induced serious support-crushing accidents; however, increasing the support strength could only provide limited control. Confined water and infiltrated modified rock mass functioned as the transfer load medium of the explosives, and the CBWDHPT fully utilized high explosion energy to break rocks. Consequently, the collapse and filling of the immediate roof and low-positioned THR, as well as the timely cutting off the middle-positioned THR, could be realized, which alleviated the migration space of THR blocks, overlying strata destruction, and earth-surface step subsidence. Finally, the environmentally friendly strategy (including the CBWDHPT and hydraulic support optimization) for overlying rock strata protection was proposed. In the industrial test, the THR was broken into blocks of different sizes after utilizing the CBWDHPT, and the support working resistance was significantly decreased. It was concluded that the environmentally friendly strategy could effectively reduce the risk of overlying rock strata destruction.